STRATEGI PEMBELAJARAN DIRIGEN DALAM MELATIH KEPEMIMPINAN PESERTA DIDIK DI MTS KECAMATAN MADANG SUKU II - Pramuja, Anggi; Kurniawan, Arif (JS (JURNAL SEKOLAH), 2025)
Abstract: This research aims to examine the conducting learning strategies implemented at MTs Madang Suku II District in fostering student leadership. Employing a qualitative approach with methods of observation, interviews, and documentation, this study found that conducting learning systematically develops leadership aspects such as self-confidence, decision-making ability, communication, and teamwork. The strategies used include the introduction of basic leadership principles in conducting, training in basic conducting techniques, the application of collaborative practice models, and evaluation and reflection. The research results indicate a significant improvement in students' leadership competencies, supported by the active role of teachers, a conducive school environment, and structured training methods. These findings suggest that arts-based extracurricular activities like conducting can be an effective platform for developing adolescent leadership character.  Keywords: Learning Strategies, Conductor/Conducting, Student Leadership, MTs Madang Suku II District.  Abstrak: Penelitian ini bertujuan untuk mengkaji strategi pembelajaran dirigen yang diterapkan di MTs Kecamatan Madang Suku II dalam melatih kepemimpinan peserta didik. Menggunakan pendekatan kualitatif dengan metode observasi, wawancara, dan dokumentasi, penelitian ini menemukan bahwa pembelajaran dirigen secara sistematis mengembangkan aspek kepemimpinan seperti kepercayaan diri, kemampuan mengambil keputusan, komunikasi, dan kerja sama tim. Strategi yang digunakan meliputi pengenalan dasar kepemimpinan dalam dirigen, pelatihan teknik dasar dirigen, penerapan model latihan kolaboratif, serta evaluasi dan refleksi. Hasil penelitian menunjukkan peningkatan signifikan pada kompetensi kepemimpinan peserta didik, didukung oleh peran aktif guru, lingkungan sekolah yang kondusif, dan metode pelatihan yang terstruktur. Temuan ini mengindikasikan bahwa kegiatan ekstrakurikuler berbasis seni seperti dirigen dapat menjadi platform efektif untuk pengembangan karakter kepemimpinan remaja. Kata Kunci: Strategi Pembelajaran, Dirigen, Kepemimpinan Peserta Didik, MTs Kecamatan Madang Suku II.